Investigating employee perceptions: Association between recognized individual talents and social wellbeing - Björk, Janina M.; Bolander, Pernilla; Forsman, Anna K. (Frontiers in Psychology, 2022)
Background: Organizations worldwide increasingly adopt inclusive talent management, and this approach appears to rhyme particularly well with the Nordic welfare model. Questions about its value remain understudied, however. The inclusive approach is rooted in positive psychology and focuses on recognizing each employee’s individual talents and assessing whether they fit the long-term needs of the organization, since a fit is assumed to be associated with employees’ well-being. In the present study, we test this assumption focusing specifically on a key talent management practice, talent identification, and the social dimension of employee well-being. Method: Data were collected through an employee survey conducted within the Finnish units of four international manufacturing organizations and analyzed using logistic regression (n=618). Results: We found that the recognition of individual talents for long-term deployment by the organization is positively associated with social well-being in terms of supervisor support and social climate in the work unit, as perceived by the employees. Conclusions: Our results tentatively suggest that inclusive talent management creates value through the identification of employees’ individual talents as this practice can be associated with their enhanced well-being.